Analisis Tindak Tutur Ilokusi Asertif dalam Film “Rumah Dinas Bapak” Karya Bobby Prasetyo - Muadzin Muadzin; Nurul Liza Aulia Rahmi; Shabira Millatina; Shalshabila Naela Azzahra; Yogiana Zahwa Walidaini; Asep Purwo Yudi Utomo; Rossi Galih Kesuma; Muhammad Noor Ahsin (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
A speech act is a medium to express an idea and emotion of a person. Speech acts have several types, one of which is illocutionary speech acts. One form of illocutionary speech acts is assertive speech acts. This assertive illocutionary speech act is found in everyday life, one of which is through movie media. The purpose of this research is to identify and describe the form of assertive illocutionary speech acts contained in the movie